SP0087 Taking Charge Patient Power. (23rd January 2014) - Higginbottom, A.
Abstract : My personal story on learning to live and self-manage my condition of Fibromyalgia. After many years of uncertainty the importance to finally receive a diagnosis. The awful realisation of being unable to work for many years and how my illness has affected my family, my whole life. Then being able to attend a Pain Management Programme at the local Rheumatology Hospital. Learning new techniques, skills and self-management that has now changed my life for the better. Which then gave me the confidence to work part time for a year to see how I managed, especially with the fatigue part of the condition. Then resulted in me being offered a part time permanent paid position Disclosure of Interest: None Declared